Solution for Information Overload Using Faceted Search-A Review - Mahdi M.N.; Ahmad A.R.; Ismail R.; Natiq H.; Mohammed M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Faceted search; Filtering technique; Heterogeneous information; Information overloading; Information overloads; Quantitative study; Theoretical framework; Web of Science; Information filtering